Photoshop 7 artistry : mastering the digital image. - Haynes, Barry, ....-; Crumpler, Wendy, ....-; Duggan, Sean, ....- (Indianapolis : New Riders, 2002)
1.Essential photoshop tools and functionality 2.Color correction and calibration to create a master digital image 3.Overall color correction, selection and layer techniques 4.Advanced color correction and restotation techniques 5.Compositing multiple images with layers, adjustment layers and layermasks 6.Calculations, patterns, filters, compositing and effects 7.Images for the web and multimedia
Keywords: Beeldbewerking; Computer graphics; Photoshop